A Sanskrit Treasury: A Compendium of Literature from the Clay Sanskrit Library, edited by Camillo A. Formigatti. (24th March 2023) - Killingley, Dermot
Abstract : A Sanskrit Treasury: A Compendium of Literature from the Clay Sanskrit Library, edited by Camillo A. Formigatti. Oxford: Bodleian Library, 2019. Foreword by Amartya Sen, preface by Richard Ovenden. xviii + 270 pp., £50. ISBN 9781851245314 (hb).